The Impact Of Credit Risk On The Profitability Of Conventional Banks In Indonesia - Rahmawati, Nur Intan; Ningsih, Indah Ayu; Muchtar, Susy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine the effect of Non-Performing Loans on profitability, to examine the effect of Capital Adequacy Ratio on profitability, to examine the effect of Total Loan to Assets Ratio on profitability, and to examine the effect of Total Loan to Deposit Ratio on profitability. The approach used in this study is quantitative with secondary data obtained from the Indonesia Stock Exchange and annual reports of companies listed on the Indonesia Stock Exchange during the period 2018 to 2023. Based on this study, it is concluded that Non-Performing Loans have a significant negative effect on bank profitability. Capital Adequacy Ratio does not affect bank profitability. Total Loan to Asset Ratio does not affect bank profitability. Total Loan to Deposit Ratio also does not affect bank profitability.